Holophytochrome-Interacting Proteins in Physcomitrella: Putative Actors in Phytochrome Cytoplasmic Signaling - Ermert, Anna Lena; Mailliet, Katharina; Hughes, Jon (Frontiers in Plant Science, 2016)
Phytochromes are the principle photoreceptors in light-regulated plant development, primarily acting via translocation of the light-activated photoreceptor into the nucleus and subsequent gene regulation. However, several independent lines of evidence indicate unambiguously that an additional cytoplasmic signaling mechanism must exist. Directional responses in filament tip cells of the moss Physcomitrella patens are steered by phy4 which has been shown to interact physically with the blue light receptor phototropin at the plasma membrane. This complex might perceive and transduce vectorial information leading to cytoskeleton reorganization and finally a directional growth response. We developed yeast two-hybrid procedures using photochemically-functional, full-length phy4 as bait in Physcomitrella cDNA library screens and growth assays under different light conditions, revealing Pfr-dependent interactions possibly associated with phytochrome cytoplasmic signaling. Candidate proteins were then expressed in planta with fluorescent protein tags to determine their intracellular localization in darkness and red light. Of 14 candidates, 12 were confirmed to interact with phy4 in planta using bimolecular fluorescence complementation. We discuss the roles these putative holophytochrome-interacting proteins (HIP's) might have in signaling.